A pilot study on the programming protocol of vagus nerve stimulation in children with drug‐resistant epilepsy: High pulse amplitude or high duty cycle - Yuying Pan; Han Xie; Jiayi Ma; Taoyun Ji; Qingzhu Liu; Lixin Cai; Yuwu Jiang; Kai Zhang; Jianguo Zhang; Ye Wu (Epilepsia Open)
Abstract Objective To compare the efficacy and safety of vagus nerve stimulation using different modes in patients with drug‐resistant epilepsy (DRE). Methods Children with DRE who underwent vagus nerve stimulator implantation between March 2019 and December 2022 were prospectively enrolled at the Peking University First Hospital. Ninety‐four children were randomly divided into the high pulse amplitude [pulse amplitude was gradually increased to maximum tolerance value (≤2.8 mA) and duty cycle was maintained at 10%] and high duty cycle groups [pulse amplitude was maintained at 1.5 mA and duty cycle was subsequently increased to maximum tolerance value (≤37%)]. At the 55‐week follow‐up, the responder rate, seizure‐free rate, and adverse effects were compared between the two groups. Results Ninety‐four children with DRE were included (47 patients each in the high pulse amplitude group and the high duty cycle group). For epileptic seizures, the responder rate of the high pulse amplitude group was 53.2% (25/47), while that of the high duty cycle group was 38.3% (18/47). High pulse amplitude had a higher responder rate of focal seizures (60.7% in the high pulse amplitude group vs. 29.2% in the high duty cycle group; chi‐squared test, p = 0.023). Among children with a ≥ 75% reduction in epileptic spasms, the high duty cycle group had a higher responder rate than the high pulse amplitude group (54.5% vs. 16.7%; Fisher's exact test, p = 0.022). In addition, in the high duty cycle group, the responder rate in children with epileptic spasms was higher than that in children without epileptic spasms (59.1% vs. 20.0%; chi‐square test, p = 0.011). Among children with implantation age <6 years, the responder rate of the high pulse amplitude group was higher (chi‐square test, p = 0.024). The incidence of adverse effects in the two groups was not statistically different. Significance The overall responder rates in the two modes were similar. The high pulse amplitude mode may be more effective for focal seizures, whereas the high duty cycle mode may be more effective for epileptic spasms. Patients aged <6 years with DRE and VNS implantation may require a higher pulse amplitude to achieve better efficacy. Plain Language Summary This study compared the anti‐seizure efficacy of two different vagus nerve stimulation (VNS) treatments. We found that the overall efficacy of the two treatments was similar. The high pulse amplitude mode may be more effective for focal seizures, whereas the high duty cycle mode may be more effective for epileptic spasms. Patients aged <6 years with drug‐resistant epilepsy (DRE) and VNS treatment may require a higher pulse amplitude to achieve better efficacy.